Mix it up! - Tullet, Herve; Franceschelli, Christopher (San Francisco, California Handprint Books, 2014)
Using no special effects other than the reader's imagination, simple directions lead the reader to experiment with mixing and changing colors on the printed page.
"Originally published in France in 2014 by Bayard Editions under the title "Couleurs"--Copyright page.
Keywords: Colors; Imagination; Fiction; Juvenile works